Factors Influencing Willingness to Donate to Marine Endangered Species Recovery in the Galapagos National Park, Ecuador - Cárdenas, Susana A.; Lew, Daniel K. (Frontiers in Marine Science, 2016)
Willingness to donate (WTD) money for the conservation of endangered species may depend on numerous factors. In this paper, we analyze data from a survey given to tourists visiting Ecuador's Galapagos National Park and Marine Reserve to investigate determinants of their WTD toward the conservation of two marine endangered species-the scalloped hammerhead shark (Sphyrna lewini) and the green sea turtle (Chelonia mydas). Specifically, we use regression analysis to analyze the influence of attitudes and beliefs toward species conservation, levels of concern for specific species, recreational motivations, and past donation patterns on WTD, while also controlling for individual characteristics such as age, gender, place of residence, and other demographics. Additionally, we evaluate the sensitivity of WTD to the species being protected by conservation efforts. Our results demonstrate that specific concern about the species, beliefs about donating to the protection program, and past donation behavior significantly influence the intention to donate money toward the recovery of the two marine endangered species. The likelihood of donating to green sea turtle conservation efforts is marginally higher than for hammerhead sharks, possibly due to its more charismatic nature. In contrast, visitors who are more willing to donate for shark conservation appear to be those with a strong desire to see them in the wild. The results provide useful information on the heterogeneity of tourist preferences toward donating to species conservation efforts, which has broad implications for resource agencies seeking ways to fund conservation actions.